Deciphering the structure of a multi-drug resistant Acinetobacter baumannii short-chain dehydrogenase reductase. - Mahdi Abedinzadeh Shahri; Paniz Shirmast; Seyed Mohammad Ghafoori; Jade Kenneth Forwood (PLoS ONE, 2024)
The rapidly increasing threat of multi-drug-resistant Acinetobacter baumannii infections globally, encompassing a range of clinical manifestations from skin and soft tissue infections to life-threatening conditions like meningitis and pneumonia, underscores an urgent need for novel therapeutic strategies. These infections, prevalent in both hospital and community settings, present a formidable challenge to the healthcare system due to the bacterium's widespread nature and dwindling effective treatment options. Against this backdrop, the exploration of bacterial short-chain dehydrogenase reductases (SDRs) emerges as a promising avenue. These enzymes play pivotal roles in various critical bacterial processes, including fatty acid synthesis, homeostasis, metabolism, and contributing to drug resistance mechanisms. In this study, we present the first examination of the X-ray crystallographic structure of an uncharacterized SDR enzyme from A. baumannii. The tertiary structure of this SDR is distinguished by a central parallel β-sheet, consisting of seven strands, which is flanked by eight α-helices. This configuration exhibits structural parallels with other enzymes in the SDR family, underscoring a conserved architectural theme within this enzyme class. Despite the current ambiguity regarding the enzyme's natural substrate, the importance of many SDR enzymes as targets in anti-bacterial agent design is well-established. Therefore, the detailed structural insights provided in this study open new pathways for the in-silico design of therapeutic agents. By offering a structural blueprint, our findings may provide a platform for future research aimed at developing targeted treatments against this and other multi-drug-resistant infections.